A manufacturing service capability publishing and trading system based on industrial internet platform. (14th June 2023) - Xiao, Rui; Xiang, Feng; Zuo, Ying; Wang, Chuangjian
With the rapid development of the industrial internet platforms, the virtualisation and ecologicalisation of manufacturing services pose new challenges to the manufacturing service capabilities, especially in terms of the improvement of publishing and transaction functions. Firstly, the demand of manufacturing service capability publishing in the market and the hierarchical structure of the industrial internet platform are analysed in this paper. Then, after defining the functional requirements, the system flow chart and the entity relationship diagram are designed. Lastly, the entire system is designed to illustrate how to publish and trade manufacturing service capabilities on the industrial internet platform.